Effect of steam reinjection mass flow rate on the SOFC–GT system with steam reinjection - Zhao, Hang; Zheng, Puyan; Zhu, Qunzhi; Zhang, Xiangpeng; Lan, Zehua; Fu, Zaiguo; Luo, Tian; Shen, Renhu; Cheng, Jiahao (Frontiers in Energy Research, 2024)
Solid oxide fuel cell is regarded as the first choice of high efficiency and clean power generation technology in the 21st century due to its characteristics of high-power generation efficiency and low pollutant emission. In this paper, hydrogen is used as a fuel for solid oxide fuel cells using the EBSILON platform. A sensitivity analysis of the Solid Oxide Fuel Cell -Gas Turbine system with steam reinjection is carried out to investigate the effect of the steam re-injection mass flow rate on the improvement of the electrical efficiency of the system as well as on the values of the other parameters.The results show that the variation of the steam reinjection mass flow rate has an effect on other parameters. Changes in several parameters affect the electrical efficiency of the system, which reaches 74.11% at a pressure ratio of 10, solid oxide fuel cell inlet temperature of 783.15 K, turbine back pressure of 70 kPa, and steam reinjection mass flow rate of 6.16 kg/s. Later research can optimize the overall parameter selection of the system in terms of economy and other aspects.